Apocrine adenosis: a precursor of aggressive breast cancer?. Issue 8 (August 1995) - Wells, C A; McGregor, I L; Makunura, C N; Yeomans, P; Davies, J D
Abstract : AIM–To investigate overexpression of c-erbB2, expression of the p53 protein product and proliferation rates in benign breast lesions with specific reference to apocrine adenosis. METHODS–Twenty one cases of apocrine adenosis were stained with monoclonal antibodies to p185, the protein product of the c-erbB2 oncogene, the protein product of the p53 tumour suppressor gene and to the cell cycle related protein Ki67. Three cases were associated with concomitant ductal carcinoma in situ of large cell type and two were associated with invasive tubular or cribriform carcinoma. RESULTS–Twelve (57.1%) cases showed membrane staining for c-erbB2 oncoprotein of apocrine cells within sclerosing adenosis and six (28.6%) had occasional p53 protein positive cells. One case not associated with carcinoma showed extensive staining of apocrine metaplasia outside the area of apocrine adenosis. The proliferation rate, as measured by Ki67 staining, was increased in some of the lesions and all lesions showed at least some of the cells to be in the cell cycle. CONCLUSIONS–The expression of abnormal oncogene products and increased proliferation in some of these apocrine lesions questions the supposed degenerative nature of the atypia seen in such cases and suggests that there may be an association between these lesions and large cell ductal carcinoma in situ and hence invasive carcinoma.